Social entrepreneurship Understanding the reality of the developing world and designing sustainable solutions - Fous, Zdeněk (2010)
Social entrepreneurship, loosely defined as delivering social value in a sustainable way using market-based principles, is especially powerful tool in the Third world. Grass-root entrepreneurial approach of developing and empowering those countries from the bottom up is proving to be the most sustainable and efficient solution. First part of this work outlines historical context of the developing world and provides thorough analysis about challenges and threats it is facing. Furthermore, model defining what countries are the "most suitable" for a social venture is described, together with tools that are used nowadays to support the developing world. Second part puts main emphasis on defining and discussing the concept of social entrepreneurship, especially with respect to social venture design. Conclusions and practical recommendations are heavily based on interviews with successful and inspirational social entrepreneurs active in the Third world, as well as with leading NGOs with offices in the Czech Republic. All in all, the ultimate goal of this work is to create a big-picture overview about the reality the developing world is facing and describe how the most sustainable solutions can be designed.